Rituximab maintenance improves overall survival of patients with follicular lymphoma: individual patient data meta-analysis - Vidal, Liat; Witzens-Harig, Mathias (European journal of cancer, 2017)
Background: Randomised trials of rituximab maintenance (MR) for patients with follicular lymphoma support improved progression-free survival (PFS), but the effect on overall survival has been inconclusive. To evaluate the effect of MR on overall survival according to patient and disease characteristics, and to explore certain adverse events, we performed an individual patient data (IPD) meta-analysis. Methods: All investigators of randomised controlled trials that compared MR therapy with observation or treatment only at relapse (no MR) for patients with follicular lymphoma were invited to participate in an IPD meta-analysis. We obtained baseline patient and disease characteristics and time to progression and death for each patient. All analyses took into account the trial and original randomised treatment group. We analysed data in two ways: a two-stage analysis and a multivariate model including patient and disease characteristics.Findings: Seven trials including 2315 patients were analysed. Overall survival of patients improved with MR compared with no MR (hazard ratio [HR] 0.79, 95% CI 0.66-0.96). We could not detect any patient or disease characteristics that were associated with a survival benefit with MR. In all of the models, MR had a beneficial effect on overall survival compared with observation for all types of patients, which was not shown in a particular subgroup in which the patient had already received rituximab in the induction phase and received first-line therapy. MR improved PFS compared with observation (HR 0.57, 95% CI 0.51-0.64). The risk of adverse events was higher with MR, specifically infection of any grade and grade 3-4 infections. Interpretation: Based on IPD from randomised controlled trials, MR improves overall survival consistently in all patients, regardless of patient and disease characteristics when compared with observation, and should be prescribed after a successful induction with R-CVP or R-CHOP for patients with follicular lymphoma. It is still uncertain if that holds when the patient has already received rituximab in his/hers first induction. The effect of MR after bendamustine-rituximab induction compared with rituximab at progression should be further explored.
Gesehen am 17.09.2018